A Further Note on Factor Substitution and Efficiency - Hanseman, Dennis J. (The Review of Economics and Statistics, 1983)
Examination of the Effects of Licensure, unpublished Ph.D. dissertation, Princeton University, 1974. DeVany, Arthur S., and Thomas R. Saving, Product Quality, Uncertainty and Regulation-The Trucking Industry,' American Economic Reviev 67 (Sept. 1977), 583-594. Gross, Donald, and Carl M. Harris, Funcdamentals of Queueing Theory (New York: Wiley, 1974). Halter, Albert N., H. D. Carter, and J. G. Hocking, A Note on Transcendental Production Function, Journal of Farm Economics 39 (Nov. 1957), 966-974. Marschak, Jacob, and William H. Andrews, Random Simultaneous Equations and the Theory of Production, Econometrica 12 (July-Oct. 1944), 143-205. Reinhardt, Uwe, A Production Function for Physician Services, this REVIEW 54 (Feb. 1972), 55-66. Scheffler, Richard M., and John E. Kushman, A Production Function for Dental Services: Estimation and Economic Implications, Southern Economic Journal 44 (July 1977), 25-35. Zellner, Arnold, Jan Kmenta, and Jacques Dreze, Specification and Estimation of Cobb-Douglas Production Function Models, Econometric a 34 (Oct. 1966), 784-795.